The role of institutional stakeholders in the success of new businesses in Africa - Arinze Nwoba; Samuel Kusi; Adedapo Adebajo; Mark Kofi Prempeh (2024)
The business startup landscape in Africa is currently experiencing massive growth. This has led to the continent becoming a hotspot for entrepreneurial activity, innovation, and investment. However, 80% of new business startups in Africa fail within their first five years of existence. To this end, this book chapter theorizes a conceptual approach positing that due to the institutional voids and unique institutional business settings in Africa, new business startups’ top-level managerial ties with relevant institutional stakeholders including political/government officials, regulatory officials, local community leaders, and business ties have a positive relationship with the growth, long-term survival, performance, and in turn, the success of new business startups on the continent. We show that these institutional stakeholders play an important role in economic and commercial activities in Africa and, as such, provide new business startups with relevant information, knowledge, and opportunities required to succeed.